Importance of cytology in the identification of villoglandular adenocarcinoma - Correia, Ana; Vilar, Madalena; Teixeira, Cidália (Citotech Online - Case Review, 2017)
Endocervical villoglandular adenocarcinoma is a rare subtype of cervical adenocarcinoma. It arises mainly in young and reproductive age women and it has a lower incidence and better prognosis compared to cervical adenocarcinoma. The present case study refers to a conventional cytology performed on a 48-year-old woman within a screening program carried out at a health center of the Local Health Unit of Matosinhos. The objective of this study is to verify the importance of the cytological sample collection method for a better observation and interpretation of the cytological findings in rare neoplastic entities, as well as to reinforce the importance of the application of complementary tests for the elaboration of a conclusive diagnosis. The cytological result of the present case report was atypical glandular cells (AGC) of the endocervical type. Subsequently, a biopsy of the uterine cervix, a conization and a curettage of endocervix were performed, whose histological diagnosis was well differentiated villoglandular adenocarcinoma from the endocervix.